2021
DOI: 10.1016/j.bja.2021.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic depth and delirium after major surgery: a randomised clinical trial

Abstract: Background: Postoperative delirium is a serious complication of surgery associated with prolonged hospitalisation, longterm cognitive decline, and mortality. This study aimed to determine whether targeting bispectral index (BIS) readings of 50 (light anaesthesia) was associated with a lower incidence of POD than targeting BIS readings of 35 (deep anaesthesia). Methods: This multicentre randomised clinical trial of 655 at-risk patients undergoing major surgery from eight centres in three countries assessed deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
147
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 27 publications
4
147
1
2
Order By: Relevance
“…It has been reported that deep anesthesia and electroencephalogram suppression were associated with the development of postoperative delirium [ 29 ]. However, it remains controversial whether anesthetic depth monitoring protects against postoperative delirium and cognitive function decline, with benefits reported in some studies [ 30 , 31 , 32 ] but not in others [ 33 , 34 ]. These contrasting results might be explained by the differences in the patient attributes, anesthetic regimens, and protocol rigor [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that deep anesthesia and electroencephalogram suppression were associated with the development of postoperative delirium [ 29 ]. However, it remains controversial whether anesthetic depth monitoring protects against postoperative delirium and cognitive function decline, with benefits reported in some studies [ 30 , 31 , 32 ] but not in others [ 33 , 34 ]. These contrasting results might be explained by the differences in the patient attributes, anesthetic regimens, and protocol rigor [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains controversial whether anesthetic depth monitoring protects against postoperative delirium and cognitive function decline, with benefits reported in some studies [ 30 , 31 , 32 ] but not in others [ 33 , 34 ]. These contrasting results might be explained by the differences in the patient attributes, anesthetic regimens, and protocol rigor [ 30 , 31 , 32 , 33 , 34 ]. Given the multiple contributing causes and inadequate understanding of pathophysiology, it is challenging to prevent or treat postoperative delirium in the high-risk population [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the statistically different incidence in POD may be interpreted as either a false positive, or due to a small between group difference in the time spent with burst suppression. In contrast, the trials by Chan et al9 and Evered et al10 investigating the relationship between pEEG-guided anesthetic depth and POD demonstrated a bigger difference in the depth of anesthesia between groups; mean BIS values between groups were 38.6 (6.5) versus 53.2 (8.9)9 and 38.7 (3.9) versus 50.7 (4.4),10 respectively. This wider group separation was associated with significant reductions in POD from 24.1% to 15.6% ( P =0.01)9 and from 28% to 19% ( P =0.01) 10…”
mentioning
confidence: 83%
“…L’étude d’Evered et al, publiée en août 2021, dans The British Journal of Anaesthesia (BJA) [7] , est une étude ancillaire de l’étude BALANCED [8] . Elle s’intéresse à l’incidence du DPO en fonction de la profondeur de l’anesthésie générale monitorée par BIS chez des patients à risque de DPO.…”
Section: Anesthésie : Publications Récentes Sur Le Délirium Postopéra...unclassified